Tuberculous lymph node in neck chain: A study of common entity at a tertiary care level in south Gujarat, Surat - Sapana S Jain; Bhoomika D Patel; Grinish P Tamakuwala; Parul K Vadgama; Chintan R Patel; Srishty M Agarwal; Rahul N Patel (Asian Journal of Medical Sciences, 2023)
Background: The microbiological diagnosis of extrapulmonary tuberculosis (TB) is quite difficult because of paucibacillary load and required radiological, cytohistopathological tests for confirmation along with clinical suspicion in case of cervical TB lymph node, body fluid examination such as pleural fluid, cerebrospinal fluid, ascitic fluid in cases of TB pleurisy, TB meningitis, and abdominal Koch’s and was quiet challenging before inclusion of CBNAAT. Aims and Objectives: The aim of the study was to study epidemiological, clinical profile and pathological diagnosis and management of TB cervical lymph node patients coming to a tertiary care center where, 60 patients were enrolled during a 2.5-month period and were followed up for 8 months. Data were entered in Microsoft Excel and analysis was done by in EP Info (version 7.0). Descriptive statistics was applied in the form of percentage, proportion, and measures of central tendency. Test of significance was applied. Materials and Methods: To study epidemiological, clinical profile and pathological diagnosis and management of TB cervical lymph node patients coming to a tertiary care center where, 60 patients were enrolled during a 2.5-month period and were followed up for 8 months. Data were entered in Microsoft Excel, and analysis was done by in EP Info (version 7.0). Descriptive statistics was applied in the form of percentage, proportion, and measures of central tendency. Test of significance was applied. Results: In this study, 23 cases (38.3%) were male and 37 cases (61.7%) were females, with a female preponderance. The mean age was 27.33 years, with a SD of 93. In this study, maximum number of cases, i.e., 44 cases (73.3%) were seen in the age group of 19–28 years. Neck swelling was the chief presenting complaint among them followed by fever, 36 patients (60%), weight loss 31 (51.7%), anorexia in 28 (46.7%), and cough in 7 patients (11.7%). 75% patients improved after taking antitubercular therapy for 6 months and 5% patients not responded to the treatment till 8 months. Conclusion: There is high incidence of TB cervical lymphadenopathy in developing countries like India.